2009
DOI: 10.1002/bjs.6670
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of folate supplementation in patients with peripheral arterial disease

Abstract: Folate administration reduced plasma homocysteine, and slightly improved ABPI and bk-PWV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 31 publications
1
48
0
1
Order By: Relevance
“…Although drugs and surgical procedures that target diseases of the elderly will hopefully arrest or partially reverse tissue damage caused by aging and chronic stress, measures to maintain health are arguably a better approach to lengthening our healthy life span. Most dietary supplement programs include combinations of vitamins, antioxidants, and other constituents, some of which have been shown to have significant health benefits in controlled clinical studies, whereas others may show adverse effects, [1][2][3][4][5][6] underscoring the need to assess functional effects of combination products. This paper presents initial data from an ongoing observational study of a novel dietary supplement program, PattonProtocol-1, which includes a natural product-derived telomerase activator targeting a fundamental aspect of cellular aging.…”
mentioning
confidence: 99%
“…Although drugs and surgical procedures that target diseases of the elderly will hopefully arrest or partially reverse tissue damage caused by aging and chronic stress, measures to maintain health are arguably a better approach to lengthening our healthy life span. Most dietary supplement programs include combinations of vitamins, antioxidants, and other constituents, some of which have been shown to have significant health benefits in controlled clinical studies, whereas others may show adverse effects, [1][2][3][4][5][6] underscoring the need to assess functional effects of combination products. This paper presents initial data from an ongoing observational study of a novel dietary supplement program, PattonProtocol-1, which includes a natural product-derived telomerase activator targeting a fundamental aspect of cellular aging.…”
mentioning
confidence: 99%
“…Third, we acknowledge that the follow-up period of 2 years is relatively short for cardiovascular outcome parameters. Our study was designed to study the effect of vitamin B12 and folic acid supplementation on PWV, and for this parameter, a 2-year intervention is considered to be sufficient, because PWV is known to respond quickly as other trials with PWV as outcome variable have shown [8,29,30]. Nevertheless, arterial stiffness is known for its limited reversibility and therefore it cannot be ruled out that differences in PWV levels may have been detected when using a longer intervention period.…”
Section: Discussionmentioning
confidence: 98%
“…This observation demonstrated that the improvement in endothelial function is due to direct pharmacologic actions of folic acid rather than reductions inHcy concentrations [32] . Another folate study performed more recently confirmed that daily supplementation of oral folic acid improves arterial function in patients with peripheral arterial disease [33] . Concerning this, a randomized study conducted in 103 patients at increased risk of stroke, investigated the effect of folic acid supplementation on carotid intima-media thickness (IMT).…”
Section: Stroke --+ +mentioning
confidence: 96%